A mammoth task: stable isotope analyses as a tool to prevent illegal trade of elephant ivory - Santos, Maria E. A.; Toropov, Pavel; Agarwal, Pihu; Frichot, Pierre Archimede Jonathan; Tilley, Hannah Bethany; Wan Zhongyue, Wilson; Chan, Jovy; Baker, David Michael (Frontiers in Ecology and Evolution, 2025)
Although mammoth ivory was claimed as a substitute to elephant ivory, there are several issues with the current methods to differentiate the two ivory, which provided a loophole to laundering and illegal trade. To contribute to developing efficient tools to distinguish ivory samples, we applied a relatively cheap and fast protocol using stable isotope ratios of carbon (δ13C), hydrogen (δ2H), nitrogen (δ15N), oxygen (δ18O), and sulfur (δ34S). We compared the isotope ratios of the two ivory types and found statistically significant (p-value<0.01) differences in the Wilcoxon tests for δ2H, δ18O, δ13C and δ34S, but no significant difference for δ15N. There was no overlap between δ2H and a small overlap for δ18O, while δ13C, δ15N, and δ34S of most mammoth samples were within the larger isotopic range values of the elephant samples. The PCA also pointed to a higher contribution of δ2H (96.9%) followed by δ18O (2.7%) to differentiate the ivory types. Our results showed SIA as an efficient tool to distinguish elephant and mammoth ivory, and we recommend using a multi-elements SIA approach focusing on δ2H and δ18O. While it is essential to address the social issues related to the ivory trade, including reducing human-elephant conflict and increasing financial support to Siberian carver communities, alternatives for natural ivory should also be sought, combined with strict policy changes to combat illegal trade and protect the African and Asian elephant populations.